2014
DOI: 10.1021/ol500531m
|View full text |Cite
|
Sign up to set email alerts
|

Direct C–H Bond Arylation of (Benzo)oxazoles with Aryl Chlorides Catalyzed by N-Heterocyclic Carbene–Palladium(II)–1-Methylimidazole Complex

Abstract: The direct C-H bond arylation of (benzo)oxazoles with aryl chlorides was achieved catalyzed by a well-defined NHC-Pd(II)-Im complex. Under the optimal conditions, various aryl chlorides were successfully applied as the arylating reagents to achieve the 2-aryl (benzo)oxazoles in acceptable to high yields, providing a convenient and alternative method for the direct C-H bond arylation of (benzo)oxazoles and enriching the chemistry of the NHC-Pd(II) complex in organic synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(26 citation statements)
references
References 76 publications
0
26
0
Order By: Relevance
“…For instance, the synthesis of [1,3-bis(2,6-diisopropylphenyl)-1H-imidazol-2(3H)-ylidene]palladium complex, from easily available starting materials in a one-pot procedure was reported [1]. In addition, the applications of this complex have been fully investigated in Suzuki-Miyaura coupling [2,[11][12][13][14][15][16][17][18], C-N coupling [1,[19][20][21], α-arylation of carbonyl compounds [22][23][24][25][26], Hiyama coupling [27], Mizoroki-Heck reaction [28] and direct C-H bond functionalization of heteroaromatic compounds [29][30][31][32][33]. As its analogue, initial studies on the catalytic activity of the title complex showed that it is also an e cient catalyst in the C-N coupling between primary and secondary amines with aryl chlorides at very low catalyst loadings, implying that the anions on the complex may have no e ect on the catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the synthesis of [1,3-bis(2,6-diisopropylphenyl)-1H-imidazol-2(3H)-ylidene]palladium complex, from easily available starting materials in a one-pot procedure was reported [1]. In addition, the applications of this complex have been fully investigated in Suzuki-Miyaura coupling [2,[11][12][13][14][15][16][17][18], C-N coupling [1,[19][20][21], α-arylation of carbonyl compounds [22][23][24][25][26], Hiyama coupling [27], Mizoroki-Heck reaction [28] and direct C-H bond functionalization of heteroaromatic compounds [29][30][31][32][33]. As its analogue, initial studies on the catalytic activity of the title complex showed that it is also an e cient catalyst in the C-N coupling between primary and secondary amines with aryl chlorides at very low catalyst loadings, implying that the anions on the complex may have no e ect on the catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in 2014, Sheo and co-workers were able to achieve a clean direct arylation of oxazoles and benzoxazoles with aryl chlorides using a well-defined palladium(II) complex C bearing an NHC and an unusual N-methylimidazole as ancillary ligand [28]. This procedure allowed the preparation of the corresponding 2-arylated (benzo)oxazoles in modest to good yields (Scheme 17).…”
Section: Direct Arylations Of Heteroarenes With Aryl Chloridesmentioning
confidence: 99%
“…Another approach to synthesizing 2-arylbenzimidazoles is metal-catalyzed direct C-H bond arylation reactions, which have emerged as one of the most efficient protocols for the synthesis of diverse 2-arylbenzimidazoles. The classical cross-coupling of benzimidazoles with aryl electrophiles catalyzed by a noble metal such as Palladium has yielded various 2-arylbenzimidazoles [17][18][19][20][21][22]. However, Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…the synthesis of diverse 2-arylbenzimidazoles. The classical cross-coupling of benzimidazoles with aryl electrophiles catalyzed by a noble metal such as Palladium has yielded various 2arylbenzimidazoles [17][18][19][20][21][22]. However, the high cost limits the scale-up development of Pd-catalyzed cross coupling reaction.…”
Section: Introductionmentioning
confidence: 99%